DOI: 10.31274/rtd-180813-5488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the loamy surficial sediments in a type area of the Iowan Erosion Surface

Abstract: Characterization of the Loamy Surficial Sediments within the Study Area 146 Origin of the sediments 148 Geomorphic and time setting 148 Loamy Sediments on the lowan Erosion Surface 150 Ruhe's Model of Landscape Evolution 152 Suggestions for Further Study of the Surficial Loamy Sediments 152 LITERATURE CITED 155 ACKNOWLEDGMENTS 163 APPENDIX A. SOIL PROFILE DESCRIPTIONS 165 List of Abbreviations 165 Texture 165 Mottles 165 Structure 165 Consistence 165 Clay films 166 Transect 4 Clay % = 26.6 e (2.79 X 10)(Distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(78 reference statements)
1
0
0
Order By: Relevance
“…The mineralogy of areas north of our study sites showed high amounts of kaolinite (Parham, 1976), which we assume were transported and deposited during the last glaciation. Similar studies have shown considerable amount of kaolinite found in the surface and subsurface horizons of soils in the Iowa Erosion Surface (Wysocki, 1983;Effland, 1990). Moreover, loess from northeast Iowa along the Mississippi river were dominated by kaolinite and illite (Ruhe, 1984;Williams et al, 2010).…”
Section: Clay Mineralogysupporting
confidence: 62%
“…The mineralogy of areas north of our study sites showed high amounts of kaolinite (Parham, 1976), which we assume were transported and deposited during the last glaciation. Similar studies have shown considerable amount of kaolinite found in the surface and subsurface horizons of soils in the Iowa Erosion Surface (Wysocki, 1983;Effland, 1990). Moreover, loess from northeast Iowa along the Mississippi river were dominated by kaolinite and illite (Ruhe, 1984;Williams et al, 2010).…”
Section: Clay Mineralogysupporting
confidence: 62%